Lung function in workers exposed to polyvinyl chloride dust. - Chivers, C P (1980)
Several reported studies on the effects of polyvinyl chloride (PVC) dust in animals and man have been conflicting. The present study of the ventilatory function of 509 male workers exposed to PVC dust was made in 1977. Altogether 104 men exposed to PVC dust only, 112 men exposed to non-chlorinated solvents only, and 293 men exposed to a mixture of both completed the MRC questionnaire on respiratory function and performed simple spirometric tests (forced expiratory volume in one second and forced vital capacity). No differences were found between the three groups after allowance was made for age, height, and smoking. When exposure and smoking effects were considered separately, the latter was shown to be the dominant cause of reduced lung function. In this study work with PVC dust has not produced deleterious effects on ventilatory function.